Rural Self Employment Training Institutes in India : A Systematic Review - Kumar, Pawan; Kumra, Ritu (Prabandhan: Indian Journal of Management, 2021)
Rural self-employment training institutes (RSETIs) came into existence in India in 2009 based on the model of rural development and self-employment training institutes (RUDSETIs). The primary aim of these institutes is to assist the unemployed youth by creating a larger ecosystem of employment through their effective training programs. Since their founding, various studies have been conducted to assess different aspects of their functioning and performance. However, no review-based study on a systematic search of literature could be noticed. This review article looked at the literature around RSETIs/RUDSETIs to address this specific research gap and thus added value to the existing body of research. The study systematically reviewed the findings of several important publications on this topic and brought out significant policy implications. The study identified certain research gaps and recommended that it was needed to measure the effectiveness of these skill development institutes and assess their direct or indirect impact on the economic growth and development of India. The study concluded that further such studies would help stakeholders measure these institutes’ genuine contribution at the macro level as an engine of growth and employment.